Assessing the genetic relationship between phimosis and 26 urogenital diseases: a Mendelian randomization study - Li, Wei; Yu, Ying; Li, Hu; Yang, Xingliang; Li, Tao (Frontiers in Endocrinology, 2024)
Purpose: To investigate the impacts of phimosis on the health of genitourinary system through Mendelian random analysis.A dual-sample Mendelian randomization (MR) analysis was conducted using the publicly available genome-wide association study (GWAS) data.The inverse variance weighted based on Random effects model (Re-IVW) method was used as the main statistical analysis. Complementary methods including weighted median, MR Egger regression, and MR pleiotropy residual sum and outlier (MR PRESSO) was applied to detect or correct the impact of horizontal pleiotropy.: Re-IVW showed a genetic predictive causal relationship of phimosis on glomerulonephritis [OR: 1.37 (1.13-1.65), p = 0.00149] and IgA glomerulonephritis [OR: 1.57 (1.18-2.09), p = 0.00187]. Suggestive evidence indicated that phimosis was associated with chronic nephritis syndrome [OR: 1.23 (1.00-1.51), p = 0.0481], acute nephritis syndrome [OR: 1.50 (1.13-2.01), p = 0.0058], and impotence [OR: 1.39 (1.11-1.73), p = 0.0035]. Kidney and ureteral stone (OR: 1.14 [1.04-1.26], p = 0.0069), urethral strictures [OR: 1.26 (1.07-1.48], p = 0.0050), benign prostatic hyperplasia [OR: 1.07 (1.01-1.13), p = 0.0242], and decreased testicular function [OR: 0.72 (0.56-0.94), p = 0.0141] have genetically predictive causal relationships.In summary, we employed a series of reliable analytical methods to investigate the association between phimosis and 26 urogenital diseases. We have reported several strong associations, but more research is needed to evaluate whether this discovery is replicated in other environments and to gain a better understanding of potential mechanisms.